Instrumental Analysis of Intrinsically Disordered Proteins 2010
DOI: 10.1002/9780470602614.ch9
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Engineered Polypeptides as a Model of Intrinsically Disordered Fibrillogenic Proteins: Deep UV Resonance Raman Spectroscopic Study

Abstract: Protein misfolding plays an important role in many neurodegenerative diseases associated with proteinaceous aggregates having an extended cross -βsheet structure. Intrinsically disordered proteins (IDPs) can also be involved in the amyloid diseases. Genetic engineering facilitates examination of folding and fi brillation mechanisms by probing the infl uence of the primary polypeptide sequence on kinetic and equilibrium properties of the protein. This chapter focuses on the use of genetic engineering in the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 211 publications
(203 reference statements)
0
6
0
Order By: Relevance
“…The design, synthesis, and folding of the polypeptide YE8 consisting of 8 repeats of a 16 amino acid monomer have been described elsewhere. ,, GAGAGA repeats form β-strands with the alternating turn groups tyrosine (Y) and glutamic acid (E) decorating the edges of the antiparallel β-sheet. After expression, purification, dialysis against doubly distilled water, and centrifugation at 15 000 g for 45 min, deep UV Raman and CD spectroscopy were used to verify disordered structure of the polypeptide at neutral pH.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design, synthesis, and folding of the polypeptide YE8 consisting of 8 repeats of a 16 amino acid monomer have been described elsewhere. ,, GAGAGA repeats form β-strands with the alternating turn groups tyrosine (Y) and glutamic acid (E) decorating the edges of the antiparallel β-sheet. After expression, purification, dialysis against doubly distilled water, and centrifugation at 15 000 g for 45 min, deep UV Raman and CD spectroscopy were used to verify disordered structure of the polypeptide at neutral pH.…”
Section: Methodsmentioning
confidence: 99%
“…Intrinsically disordered proteins (IDPs), which lack stable secondary or unique tertiary structure under physiological conditions, play a crucial role in a large variety of human diseases ranging from neurodegenerative disorders to systemic amyloidosis as well as in a variety of other diseases . Transitions of α-synuclein, amyloid β peptide, tau-protein, prion protein, huntingtin protein with polyQ expansion, islet amyloid polypeptide, or atrial natriuretic factor, among others, from soluble, natively unfolded forms into insoluble plaques consisting of β-sheet-rich amyloid fibrils are associated with pathological evidence of Parkinson’s disease, Alzheimer’s disease, spongiform encephalopathies, Huntington’s disease, type II diabetes, or atrial amyloidosis. Whereas the precise molecular mechanisms of amyloid fibrillation remain elusive, the process typically begins with the formation of a monomeric amyloidogenic conformation, followed by nucleation (formation of specific aggregation-prone oligomers) and propagation to form proto-fibrils and proto-filaments, and finally mature fibrils. Protein fibrillation is highly dependent on the initial protein structure (folded or unfolded), amino acid sequence, concentration, pH, or environmental conditions. After reviewing data for the amyloidgeneses of more than 20 IDPs, both related and unrelated to human disease, we found that in contrast with compact globular proteins that require partial unfolding prior to the subsequent structural rearrangements and aggregation eventually leading to the amyloid fibril formation, partial folding is an obligatory prerequisite for the initiation of IDP amyloidogenesis. ,, Our work addresses one of the key issues in the amyloid fibrillation of IDP where structural rearrangements are not constrained by the initial conformation, which is the transformation of a polypeptide at global and secondary structural levels in the early stages of fibrillation. Recently, it was demonstrated that the de novo, genetically engineered polypeptide GH 6 [(GA) 3 GY(GA) 3 GE} 8 GAH 6 (YE8) is intrinsically disordered and exhibits all of the properties of a typical fibrillogenic protein.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously YEHK21 was shown to rapidly form β-sheet assemblages (refolds in ∼1 h after melting) that condense into well-defined fibrillar structures on incubation at pH 6.5. 41,64,66 However, at pH 6.5 YE8 does not form fibrils. Only following incubation at pH 3.5 for a longer period (∼45 days) does YE8 form well-defined fibrillar structures.…”
Section: ■ Introductionmentioning
confidence: 94%
“…Both YEHK21 and YE8 form identical GAGAGA β-strands. Previously YEHK21 was shown to rapidly form β-sheet assemblages (refolds in ∼1 h after melting) that condense into well-defined fibrillar structures on incubation at pH 6.5. ,, However, at pH 6.5 YE8 does not form fibrils. Only following incubation at pH 3.5 for a longer period (∼45 days) does YE8 form well-defined fibrillar structures. , In a previous study on charge distribution using YEHK21 and YE8, it was found that the precise distribution of electrostatic interactions within polypeptides, rather than simply the reduction or elimination of these interactions, can promote amyloid fibril formation .…”
Section: Introductionmentioning
confidence: 98%